AN ENHANCEMENT OF KRIGING BASED FINITE ELEMENT FOR PLATE ANALYSIS BY USING MITC3+ ELEMENT - Sebastian Sebastian; Wong Foek Tjong (Program Studi Magister Teknik Sipil - Petra Christian University, 2021)
A development of Kriging-based finite elements method has been carried out by implementing the MITC3+ plate elements for modeling the plate structure. The MITC3+ element used is a development of the MITC3 element whose performance is considered quite good and can overcome problems that arise in the application of conventional Kriging-based finite elements, one of which is the shear-locking. The application of Kriging interpolation on MITC3+ elements is carried out with the Kriging shape function formulation in the formation of the bending stiffness matrix only. The elements are then tested with various benchmark problems such as Patch Test, hard clamped square plate, Rhombic Plate, and its ability to solve complex-shaped plates. The results showed that the MITC3+ was able to avoid the shear-locking mechanism and also produce an accurate solution. However, it appears there is an inconsistent convergence pattern on the Patch Test and Rhombic Plate.